Pengaruh Pendapatan dan Konsumsi Rumah Tangga terhadap Kesejahteraan Keluarga Buruh Tambak Benih Bandeng Desa Penyabangan - Mila Faizah; M. Rudi Irwansyah (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study to analyse the effect of income and haoshold consumption on the walfare of milkfish fry pond laborers’ families in Penyabangan Village. As a vulnerebable economy group, it is essensial to understand how income and consumption contribute to their family walfare. The research uses a quantitative approach with data collected through questionnaires distributed to milkfish fry pond laborers in the area. The data were analyzed using multiple linear regression. The result show that both income and haousehold consumption have a positive and significant effect on family walfare. These finding indicate that increasing income and managing haousehold consumption effectively can improve the welfare of pond laborers’ families in Penyabangan Vilage. This study is expected to provide input for local goverments and stakeholders in formulating policies to support the well baing of pond-based family welfare.